The Change of Gender Influence Language Features Used by Transgender in The Danish Girl Movie - Rahayu, Ni Nyoman Putri; Detriasmita Saientisna, Made; Seri Malini, Ni Luh Nyoman (Stilistika : Journal of Indonesian Language and Literature; Vol 2 No 2 (2023): Volume 2 No 2, April 2023DO - 10.24843/STIL.2023.v02.i02.p10, 2023)
This study was aimed to finding and discuss about the affection of the change of gender in terms of language features used by Einar Wegener with masculine gender and after changing gender into Lili Elbe with feminine gender. The frequency of use of each language feature reduced by 31 in Einar's data and 29 in Lili's data, according to a comparative analysis of the affection of men-to-women identity transformation. As a result, the language features of transgender woman, Lili Elbe, were found to dominantly use women's language features, despite the fact that three of the five features used men's language features. Hence, it was proven that Lili Elbe's transformation from a man to a woman had influence on her language features, which was followed by a change in gender from masculine to feminine due to the influence of an environment dominated by women and influenced by feminine topics of conversation.